The great depression revisited : essays on the economics of the thirties - Van Der Wee, Herman (The Hague : Nijhoff, 1972)
The study of the depression of the thirties ;it allows a fruitful comparison with the present state of monetary crisis in the world and wits related political,commercial,and financial problems
Some articles have been translated from the Dutch.
Includes bibliographical references and index.
obn 23/01/2019
Loans
Keywords: Depressions